Recent US offshore oil and gas lease bidding: A progress report - Philip Haile; Kenneth Hendricks; Robert Porter (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2009)
This paper describes an ongoing research project, in which we examine recent trends in bidding for offshore oil and gas leases, and the exploration and development of leases after they are sold. We review empirical findings regarding bidder participation and bidding for the period 1954 through 1982. In 1983, the MMS adopted Area Wide Leasing (AWL), which dramatically changed the bidding environment. We provide an initial analysis of the post-1982 data, documenting a number of significant changes in behavior and outcomes. Bidding has been much less aggressive recently in comparison with the early years of the leasing program, in terms of both the number of bids submitted and the level of the submitted bids. This descriptive evidence leads to a number of questions, and we discuss a number of changes in the bidding environment since 1982, which may offer partial explanations of the observed changes.
Keywords: 330; Offshore-Industrie; Förderkonzession; Auktion; USA